Case Report: Pneumonia Provocate Thyroid Storm in Graves Disease - Hermawati, Berty Denny; Prabowo, Nurhasan Agung; Putri, Desy Puspa; Myrtha, Risalina; Apriningsih, Hendrastutik (Smart Medical Journal, 2023)
Introduction: A thyroid crisis is an endocrine emergency involving many organ systems and can be fatal to the patient's survival. Although cases of thyroid crisis are rare, the mortality rate is significant which reaches 20–50%. The presence of comorbidities such as pneumonia infection increases the risk of death dramatically. Infection is a factor that can trigger thyroid crisis and exacerbate thyrotoxicosis. This condition of thyroid crisis most often occurs in people with hyperthyroidism caused by Graves' disease. We present the case of a patient with Graves' disease, aged 22 years, who developed a thyroid crisis due to community-acquired pneumonia infection. This study aims to provide a case report regarding the thyroid crisis due to pneumonia.Results: We carried out a physical and some appropriate supporting examinations to confirm the diagnosis. Wayne's index was 26, indicating hyperthyroidism. Assessment with Burch-Wartofsky obtained a score of 45, indicating suspicion of a thyroid storm. Then supportive care was provided to the patient. The community-acquired pneumonia as a triggering factor was treated with antibiotics. Thyrotoxicosis conditions were treated with antithyroid, beta-blocker, and glucocorticoid drugs. The patient's condition improved after treatment.Conclusion: It is crucial to detect and treat thyroid storm as quickly as possible since it has a high mortality rate. Wayne's score is useful for identifying hyperthyroidism based on clinical symptoms. The Burch-Wartofsky Point Scale scores are used to diagnose thyroid storms. Thyroid storm should be managed according to PERKENI (Perkumpulan Endokrinologi Indonesia) and ATA (American Thyroid Association) recommendations. This case serves as an example of how to make a proper diagnosis and treatment to prevent morbidity and death due to thyroid crisis.